A new adaptive controller for volume-controlled mechanical ventilation in small animals. (1st May 2014) - Huhle, Robert; Spieth, Peter M.; Güldner, Andreas; Koch, Thea; Abreu, Marcelo Gama de
ABSTRACT: Background : This study aimed to develop and evaluate an adaptive control system for volume-controlled ventilation (VCV) in small animals to guarantee accurate delivery of tidal volume ( V T ) in the presence of changes in lung mechanics. Methods : The adaptive control system to control the Harvard Inspira ventilator was designed and evaluated on a custom-made physical model during step changes of resistance and elastance of the respiratory system assessing difference in minute ventilation (ΔMVc ) during convergence cycles ( N C ). The controller was then evaluated during conventional and variable volume VCV in rats with acute respiratory distress syndrome (ARDS) induced by intratracheal HCl (six animals/group), where the difference between desired and applied V T (d V T, d ), its root-mean square error (RMSE) and relative deviation from target minute ventilation (ΔMV) were determined. Results : The controller showed fast convergence N C < 20 cycles with an acceptable ΔMVC < 10% in simulations and nearly abolished d V T, d (VCV: 0.23 ± 0.1 mL to 0.0 ± 0.0 mL, P < .001 and v V CV: 0.05 ± 0.8 mL to 0.0 ± 0.0 mL, P < .001), significantly reduced RMSE (VCV: 0.23 ± 0.1 to 0.04 ± 0.01 mL, P < .001 and v VCV: 0.13 ± 0.04 to 0.08 ± 0.02 mL, P < .001) and ΔMV (VCV: 11.6 ± 4.2 to 0.04 ± 0.15%, P < .001 and v VCV: −3 ± 3.8 to −0.35 ± 1.3 %, P < .001) in animal experiments. In VCV the improvement was more pronounced, due to reduced respiratory system elastance in this group (VCV: 5.6 cmH2 O mL −1 versus v VCV: 3.8 cmH2 O mL −1, P < .001). Conclusions : The new adaptive controller ensured accurate delivery of V T in VCV and proved valuable for mechanical ventilation of small animals especially in ARDS research.